Effects on how corn distiller grains with solubles (DDGS) as a replacement for soybean meal (SBM) in a Boer goat diet can improve profitably for producers by saving $0.17 per lbs. of feed - Budinas, Alishah H.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Forty-eight Boer goats were fed a DDGS diet, to which replaced the common SBM diet through 4 separate treatments (Exp. 1 to 4). The experiment is based on evaluating the efficacy of corn dried distiller grains with solubles (DDGS) as a replacement for soybean meal (SBM) in a Boer goat diet to determine growth performance, diet digestibility, carcass traits, and how these outcomes influence profitability for feed producers. Goats were fed a pelleted concentrated diet at Kansas State University’s Sheep and Goat Unit. These feeds either contained no DDGS in replace of SBM (Exp. 1), 33% DDGS in replace of SBM (Exp. 2), 66% DDGS in replace of SBM (Exp. 3), 100% DDGS in replace of SBM (Exp. 4). The study had 16 pens total dedicated to each treatment, with 4 pens containing 3 goats in each. These goats were fed twice a day along with weighing weekly from 0 d to 47 d; 0 d being the start of the experiment. On d 47, the lowest and highest weighed goats were taken out of each corresponding pen for carcass evaluations (hot carcass weight, carcass yield, loin eye area, loin eye depth, back fat, and body wall thickness). After Boer goats were slaughtered, the GLIMMIX procedure of SAS determined the data regarding growth performance (body weight, average daily gain, average daily feed intake, and gain to fed ratio). Overall, carcass traits, growth performance, and feed efficiency had results of acute change in numbers, indicating DDGS lacked the opportunity to cause unnecessary weight gain or loss in goats. From a marketing standpoint, when balancing Exp. 4’s diet compared to Exp. 1; there is a $56.23/ton saving in formulating the feed; converting to $0.17/lbs. basis. Overall, Exp. 4 with only DDGS affected the absence of goat’s comprehensive hot carcass weight and average daily gain in a sustainable and more profitable way. In conclusion, 100% DDGS in Exp. 4 showed no significant negative differences in the goats compared to the usual soybean meal diet in Exp. 1.
Keywords: Spring 2018